2018
DOI: 10.1038/s41598-018-23342-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential regulatory mutations using multi-omics analysis and haplotyping of lung adenocarcinoma cell lines

Abstract: The functional relevancy of mutations occurring in the regulatory regions in cancers remains mostly elusive. Here, we identified and analyzed regulatory mutations having transcriptional consequences in lung adenocarcinoma-derived cell lines. We phased the mutations in the regulatory regions to the downstream heterozygous SNPs in the coding regions and examined whether the ChIP-Seq variant tags of the regulatory SNVs and the RNA-Seq variant tags of their target transcripts showed biased frequency between the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…We show an example of revealing a complex SV, where a large inversion and two flanking deletions to the reference genome are identified as two SVs, each of which connects two different points on a chromosome (i.e., INV or BND record in VCF). Previous studies involving the use of whole genome sequencing or RNA-seq by using Illumina HiSeq or Nanopore MinION, identified the CCDC6-RET fusion gene in LC-2/ad (Suzuki et al 2014(Suzuki et al , 2015(Suzuki et al , 2017Sereewattanawoot et al 2018). However, those studies focused only on the region around the CCDC6-RET fusion point, and the entire picture, including the other end of the inversion, was unclear.…”
Section: Revealing a Large Sv: A Large Inversion And A Subsequent Short Deletionmentioning
confidence: 99%
“…We show an example of revealing a complex SV, where a large inversion and two flanking deletions to the reference genome are identified as two SVs, each of which connects two different points on a chromosome (i.e., INV or BND record in VCF). Previous studies involving the use of whole genome sequencing or RNA-seq by using Illumina HiSeq or Nanopore MinION, identified the CCDC6-RET fusion gene in LC-2/ad (Suzuki et al 2014(Suzuki et al , 2015(Suzuki et al , 2017Sereewattanawoot et al 2018). However, those studies focused only on the region around the CCDC6-RET fusion point, and the entire picture, including the other end of the inversion, was unclear.…”
Section: Revealing a Large Sv: A Large Inversion And A Subsequent Short Deletionmentioning
confidence: 99%
“…After validating the method using the trisomy cell line data, they applied the method to clinical samples, and successfully identified an allelic imbalance derived from the SVs and aneuploidy in a colorectal cancer genome. In 2018, Sereewattanawoot et al, in our work group, reported the haplotype phasing of 23 lung adenocarcinoma cell lines using linked-read sequencing [23] . They validated the results of the phasing using ONT MinION sequencing, and attempted to identify an association between the regulatory mutations and their transcriptional consequences using haplotype phasing and previously generated multi-omics information of whole-genome, transcriptome, and epigenome sequencing data, including DNA methylation and eight histone modifications [84] .…”
Section: Haplotype Phasing and Svsmentioning
confidence: 99%
“…This approach is known as linked-read technology. This technology had a great impact on the analysis of haplotype phasing and large genomic rearrangements [21] , [22] , [23] . However, 10X Genomics has discontinued the production of the linked-read sequencing method.…”
Section: Introductionmentioning
confidence: 99%
“…This complex SV can be considered a large inversion and two deletions flanking the reference genome. Previous studies involving the use of whole genome sequencing or RNA-seq with the Illumina HiSeq or Nanopore MinION identified the CCDC6-RET fusion gene in LC-2/ad [1719, 31]. However, those studies focused only on the region around the CCDC6-RET fusion point, and the entire picture, including the other end of the inversion, was unclear.…”
Section: Visualization Examplesmentioning
confidence: 99%
“…First, we sequenced the genome of LC-2/ad with Oxford Nanopore MinION R9.5 pore chemistry and merged reads with those from a previous study (accession No. DRX143541-DRX143544) [31]. We generated 3.5 M reads to 12.8× coverage in total and then aligned them with GRCh38.…”
Section: Visualization Examplesmentioning
confidence: 99%